Pharmacokinetics of oral tenofovir disoproxil fumarate in pregnancy and lactation: A systematic review - Bierhoff, M; Smolders, EJ; Tanning, J; Burger, DM; Spijker, R; Rijken, MJ; Angkurawaranon, C; McGready, R; White, NJ; Nosten, F; van Vugt, M (International Medical Press, 2019)
Background: Tenofovir disoproxil fumarate (TDF), the oral prodrug of tenofovir (TFV), is advocated in pregnancy for prevention of mother-to-child transmission (PMCT) with failure of hepatitis B immunoglobulin and vaccination. The pharmacokinetics of TDF monotherapy for PMCT-HBV is important if deployment is to emulate the success of multiple antiretrovirals (ARVs) for PMCT-HIV in resource-constrained settings.